Evaluation of Energy Demands and Performance of Multi-Storey Cross-Laminated Timber Buildings - Timothy O. Adekunle (Energies)
The overarching goal of this research is to evaluate the energy demands and performance of multi-storey cross-laminated timber (CLT) buildings. The research examines the various energy demands influencing the performance of multi-storey CLT buildings. The study addresses the following research question: Can different energy demands influence the performance of CLT buildings? The investigation explores building modeling and simulation under two different weather scenarios to assess these issues. The study considers London Islington and St Albans (Test Reference Year—TRY), due to the proximity of the actual case studies to the reference locations of the weather files. The investigation captures energy demands and performance in the warm season (i.e., May–August). The findings show that the Stadt building (STB) temperatures under the two weather scenarios are warmer by 1.2 °C and 1.6 °C than those of Brid building (BDH) under the same weather conditions. Outdoor dry-bulb temperatures have a lesser impact on radiant temperatures than indoor air temperatures and operative temperatures in the buildings. Solar gains for external windows are influenced by design variables (e.g., building shapes, heights, floor areas, orientations, opening sizes, etc.). The indoor environmental conditions of the buildings under different weather conditions are comfortable, except for BDH St Albans TRY. Occupancy is a major driver influencing domestic hot water (DHW) usage profiles, regardless of the energy sources in the buildings. DHW is a significant parameter determining the overall energy usage in buildings. Other energy usage profiles, such as room electricity, computers and equipment, general lighting, and lighting, can also impact energy usage in buildings. The research outcomes can enhance our understanding of energy usage profiles and possible improvements to enhance the overall performance of CLT buildings.